Incidence and outcome of acute kidney injury after open heart surgery in children - Krastins, Jekabs; Straume, Zane; Auzins, Janis; Petersons, Aigars; Petersons, Aivars (Acta medica Lituanica, 2012)
Introduction. Cardiac surgery with cardiopulmonary bypass (CPB) is commonly perceived as a risk factor for decline in renal function. Hypothermia, hypoxia, hypotension, non-pulsatile blood flow during CPB, use of ACE inhibitors, inotropic and (or) vasoactive support affect kidney and contribute to the acute kidney injury (AKI). Objective. To evaluate incidence and outcome of AKI in children undergoing open heart surgery. Methods. We conducted a prospective, non-randomized observational study at the tertiary care of the University Children’s Hospital Pediatric ICU. We enrolled 30 patients, 12 boys and 18 girls with CHD. Their median body weight was 6.8 kg (IQR 5.2